A cross-sectional study on the effect of dietary zinc intake on the relationship between serum vitamin D3 and HOMA-IR - Hu, Biao; Lin, Zheng-yang; Cai, Yuan; Sun, Yue-xin; Yang, Shu-qi; Guo, Jiang-long; Zhang, Shi; Sun, Dong-lin (Frontiers in Nutrition, 2022)
Introduction Serum vitamin D3 concentration is associated with the risk of insulin resistance. Zinc has also been reported to be associated with a lower risk of insulin resistance. In addition, zinc is an essential cofactor in the activation of vitamin D3. However, the effect of dietary zinc intake on the relationship between vitamin D3 and insulin resistance risk has not been fully studied. Therefore, we designed this cross-sectional study to assess the impact of changes in zinc intake on the relationship between vitamin D3 and insulin resistance risk. Study design and methods This study analyzed data from the national Health and Nutrition Examination Survey (NHANES) from 2005 to 2018, involving 9,545 participants. Participants were stratified by zinc intake category (low zinc intake <9.58 mg/ day; High zinc intake: ≥9.58 mg/ day). Results In this cross-sectional study, serum vitamin D3 levels were independently associated with the risk of insulin resistance in both the low and high Zinc intakes (β: −0.26, 95%Cl: −0.56 0.04 vs. β: −0.56, 95%Cl: −1.01 -0.11). In addition, this association was influenced by different dietary zinc intakes (interaction P < 0.05). Conclusions Our results suggest that zinc intake may influence the association between serum vitamin D3 and the risk of insulin resistance. Further randomized controlled trials are needed to provide more evidence of this finding.